Imām al-Māwardī’s View on the Concept of Taxation (Kharaj) in al-Aḥkām Sultḥāniyyah - Rahmad Hakim; Ririn Noviyanti (Journal of Islamic Thought and Civilization, 2024)
Throughout the course of history, spanning centuries, taxation (kharāj) as sources of income of the state is significantly influential in the development of Islamic civilization. Within Islamic civilization, various principles governing the fundamental aspects of the state system, specifically in finance (fiscal and monetary) are formulated. The policy regulating state finance, with a particular focus on taxation, serves as evidence of the foundational principles of Islamic governance aimed at achieving justice and welfare for the people. The state taxation system arose due to the expansion of Islamic territories and the acquisition of spoils of war obtained by Muslims, whether through peace treaties (fay’) or warfare (ghanīmah). Therefore, this research aimed to analyze the concept of taxation in Islam, with a particular focus on al-Aḥkām as-Sultḥāniyyah by Imām al-Māwardī. The conclusion drawn was that the theory of taxation had several advantages; firstly, the thoughts of Imām al-Māwardī regarding taxation were forward-looking, specifically in terms of the flexibility in determining the tax object by adapting it to the conditions of the tax object and subject. Secondly, the imām's conceptualization of taxation remained highly contextual, making it relevant for contemporary application.